2003
DOI: 10.1515/znc-2003-7-818
|View full text |Cite
|
Sign up to set email alerts
|

Lignans, Phenylpropanoids and Polyacetylenes from Chaerophyllum aureum L. (Apiaceae)

Abstract: Sub-aerial parts of Chaerophyllum aureum L. yielded two polyacetylenes, falcarinol (1), falcarindiol (2), three lignans, namely nemerosin (3), deoxypodorhizone (4), deoxypodo-phyllotoxin (5), two phenylpropanoids, 1Ј-hydroxymyristicin (6) and its angeloyl ester (7). Compounds 6 and 7 were isolated for the first time from plant material and their structures were elucidated by means of extensive 1-and 2-dimensional NMR spectroscopy and high resolution mass spectrometry. In bioautographic tests on TLC plates the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
9

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 1 publication
1
16
0
9
Order By: Relevance
“…Its aerial parts are frequently used in food and cheese preparations and also as an edible vegetable in Iran and Turkey (Coruh, Sagdicoglu Celep, & Ozgokce, 2007;Dini & Babakhanlou, 2002;Durmaz, Sagun, Tarakci, & Ozgokce, 2006;Mozaffarian, 1996). Phytochemical investigations on Chaerophyllum species have demonstrated the presence of lignans, phenylpropanoids and polyacetylenes (Mikaya, Turabelidze, Kemertelidze, & Wulfson, 1981;Rollinger, Zidorn, Dobner, Ellmerer, & Stuppner, 2003), phenolic acids and related compounds (Dall'Acqua, Viola, Piacente, Cappelletti, & Innocenti, 2004), flavonoid glycosides (Gonnet, 1983(Gonnet, , 1986 and carbohydrates (Ayala Garay, Briard, Peron, & Planchot, 2003) in these plants. However, except for two reports from Turkey, one on the antioxidant (Coruh et al, 2007) and the other on the antibacterial (Durmaz et al, 2006) activity of C. macropodum, no studies regarding its bioactivity have yet been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…Its aerial parts are frequently used in food and cheese preparations and also as an edible vegetable in Iran and Turkey (Coruh, Sagdicoglu Celep, & Ozgokce, 2007;Dini & Babakhanlou, 2002;Durmaz, Sagun, Tarakci, & Ozgokce, 2006;Mozaffarian, 1996). Phytochemical investigations on Chaerophyllum species have demonstrated the presence of lignans, phenylpropanoids and polyacetylenes (Mikaya, Turabelidze, Kemertelidze, & Wulfson, 1981;Rollinger, Zidorn, Dobner, Ellmerer, & Stuppner, 2003), phenolic acids and related compounds (Dall'Acqua, Viola, Piacente, Cappelletti, & Innocenti, 2004), flavonoid glycosides (Gonnet, 1983(Gonnet, , 1986 and carbohydrates (Ayala Garay, Briard, Peron, & Planchot, 2003) in these plants. However, except for two reports from Turkey, one on the antioxidant (Coruh et al, 2007) and the other on the antibacterial (Durmaz et al, 2006) activity of C. macropodum, no studies regarding its bioactivity have yet been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…GC-FID measurements were carried out on a capillary column (30 m × 0.25 mm i.d). The presence of lignans, phenylpropionoids and polyacetylenes (Rollinger et al, 2003), phenolic acids in the essential oils was demonstrated. Injector and detector temperatures were 220 • C and 250 • C, respectively.…”
Section: Essential Oils With Favourable Biological Actionsmentioning
confidence: 97%
“…Antiviral activity was also demonstrated (Hudson, ). Antifungal and spore germination inhibiting properties are well known (Rahman et al ., ; Olsson and Svensson, ; Hansen and Boll, ; Harding and Heale, , ; Garrod and Lewis, ; Kemp, ), as are the effects against bacteria and mycoplasma (Schinkovitz et al ., ; Lechner et al ., ; Rollinger et al ., ; Bae et al ., ; Kobaisy et al ., ; Muir et al ., ).…”
Section: Introductionmentioning
confidence: 99%